Internationalization of higher education in a flat world: A Malaysian perspective - Murad Sani, Azlina; Awang Hashim, Rosna; Ishak, Mohamed Mustafa; Chan, Victor K.K (2011)
This paper outlines Malaysian perspectives and responses to the global needs of higher learning in a "flat world" (Friedman, 2006). In Malaysia, internationalization is contextualized within a comprehensive, long term national strategic plan for the development of higher education. Hence, while strategies for internationalization may differ, public higher education institutions work towards common goals.The paper reports national level rationales and strategic objectives for the intensification of internationalization. It highlights how these have been translated by Universiti Utara Malaysia to increase its international visibility, enrich the experiences of its students as well as strengthen curricular standards. Challenges in internationalizing higher education are also discussed.